BODY IMAGE PERCEPTION, BARBELL ROMANIAN DEADLIFT AND HIP THRUST EXERCISE ON GLUTES MUSCLE HYPERTHROPY IN WOMEN - Hasibuan, Adinda Zahrunnisa; Susanto, Indra Himawan; Mustar, Yetty Septiani; Sulistyarto, Soni; Bahauddin, Muhammad Arja; Ockta, Yovhandra (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
Most women often feel unease with their body image as it is an asset for their attractiveness, this refers to the perception of body image. When observed, most female members in Recharge Functional Training have the same feeling about their body image, also have the same desire to have an ideal body shape with specific muscle growth, especially buttocks area. The purpose of this study is to determine the perception of body image, comparing the effect of romanian deadlift and hip thrust exercises on glutes muscle hypertrophy of female member. The research method uses quantitative descriptive using two group pre-posttest design. Population includes female participants of Recharge Functional Training, with total of 8 samples. Data collection instruments using body image satisfaction questionnaires, romanian deadlift and hip thrust programs by measuring hip circumference in samples to determine pre-posttest values. Results shows that the perception of body image satisfaction in women is high with value of 100%. There was an increase in the growth of glutes muscle mass in sample A group with romanian deadlift, but none was found in sample B group with hip thrust exercise program. Furthermore, there is no average comparison to post-test results from these 2 sample groups.